2013
DOI: 10.1111/ans.12110
|View full text |Cite
|
Sign up to set email alerts
|

New treatment sequence protocol to reconstruct locally advanced breast cancer

Abstract: Our new treatment sequence protocol offers a simpler, more advantageous approach to LABC. We hypothesize equivalent oncological efficacy, optimized oncological management and surgical planning. The aim was to shorten and simplify the reconstructive journey through a single operation including gold-standard reconstruction, offering better cosmesis, fewer complications and reduced costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Neoadjuvant radiotherapy increases tumor resectability, and adjuvant radiotherapy is used to decrease local recurrence. If negative local effects of radiotherapy are present in the flaps after radiotherapy, autologous flaps can be considered after primary surgery for LABC . TAFs allow skin closure and radiotherapy, and autologous flaps can be performed later.…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant radiotherapy increases tumor resectability, and adjuvant radiotherapy is used to decrease local recurrence. If negative local effects of radiotherapy are present in the flaps after radiotherapy, autologous flaps can be considered after primary surgery for LABC . TAFs allow skin closure and radiotherapy, and autologous flaps can be performed later.…”
Section: Discussionmentioning
confidence: 99%
“…Although this definition may underestimate the number of patients who received NRT, we believe that this limitation is reduced considering that the current practice trend is for patients to undergo surgery 6 weeks post-NRT completion. 5 Nevertheless, for the cohort receiving NRT, we were unable to determine the exact timing of radiotherapy (ie, NRT was delivered in the 90 days preceding the surgery, but this could range from 1–12 weeks before the surgery).…”
Section: Discussionmentioning
confidence: 99%
“…3, 4 As compared with NCT alone, the combination of NRT and NCT promoted complete pathological response, clinical remission, and increased median survival. 5 This has allowed breast-conserving surgery to be performed with enhanced safety and frequency, with rates reaching 43–92%. 610 Isolated NRT has also been found to promote favorable long-term survival among women undergoing breast-conserving surgery 11, 12 or mastectomy.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published a protocol for treatment of locally advanced breast cancer with autologous breast reconstruction that is simpler, shorter and results in a good cosmetic outcome as compared with traditional protocols …”
Section: Introductionmentioning
confidence: 99%
“…12,13 We have previously published a protocol for treatment of locally advanced breast cancer with autologous breast reconstruction that is simpler, shorter and results in a good cosmetic outcome as compared with traditional protocols. 14 Within this algorithm, the patients are treated with preoperative neoadjuvant chemotherapy and then with radiation before the mastectomy. Numerous reports have shown that this is oncologically safe.…”
Section: Introductionmentioning
confidence: 99%